Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1248/bpb.b13-00768
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Complex of Plasmid DNA Electrostatically Assembled with Polyamidoamine Dendrimer and Chondroitin Sulfate for Effective and Secure Gene Delivery

Abstract: The purpose of this study was to develop a ternary complex of plasmid DNA (pDNA) electrostatically assembled with polyamidoamine (PAMAM) dendrimer and chondroitin sulfate (CS) for effective and secure gene delivery. PAMAM dendrimers are new cationic polymers that are expected to be used as gene delivery vectors. However, cationic non-viral gene vectors showed cytotoxicity by binding to negative cellular membranes. We therefore prepared a ternary complex by adding CS, an anionic polymer, and examined its useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Iwanaga et al also reported that intravenous administration of ternary complexes of pDNA/ dendrigraft poly-L-lysine/CS ( Figure 5A) induced high gene expression levels in the reticuloendothelial system [63]. Furthermore, Imamura et al reported that a ternary complex of pDNA electrostatically assembled with PAMAM dendrimer and CS ( Figure 5A) was an effective and secure gene vector, and they led to signi icantly higher gene expression in the spleen than pDNA/PAMAM dendrimer polyplexes [64]. Therefore, CS coating of polyplexes may be expected to be useful for gene vectors to the spleen, and they may be a promising approach for DNA vaccination.…”
Section: Lo Et Al Reported That Cs-modi Ied Pei/pdna (mentioning
confidence: 96%
“…Iwanaga et al also reported that intravenous administration of ternary complexes of pDNA/ dendrigraft poly-L-lysine/CS ( Figure 5A) induced high gene expression levels in the reticuloendothelial system [63]. Furthermore, Imamura et al reported that a ternary complex of pDNA electrostatically assembled with PAMAM dendrimer and CS ( Figure 5A) was an effective and secure gene vector, and they led to signi icantly higher gene expression in the spleen than pDNA/PAMAM dendrimer polyplexes [64]. Therefore, CS coating of polyplexes may be expected to be useful for gene vectors to the spleen, and they may be a promising approach for DNA vaccination.…”
Section: Lo Et Al Reported That Cs-modi Ied Pei/pdna (mentioning
confidence: 96%
“…They also claim comparable or superior transfection efficacies with fluorinated G3, G4, and G5 PPI dendrimers as compared with Lipofectamine 2000, branched poly(ethyleneimine), SuperFect ® , PolyFect ® , as well as argininemodified dendrimer on both HEK293 and HeLa cells (Liu et al 2014a). The ternary complex of plasmid DNA polyamidoamine dendrimer and chondroitin sulfate results in no agglutination activity and no cytotoxicity against B16-F10 cells (Imamura et al 2014). PEGylation is the well-known method to improve biocompatibility and transfection efficiency (Sun et al 2014).…”
Section: Cationic Dendrimersmentioning
confidence: 97%
“…To determine the pathway of R13 internalization, we preincubated cells with 80 μmol dynasore (inhibitor of clathrin-mediated endocytosis) [23], 50 μmol genistein (inhibitor of caveolae-mediated endocytosis) [24], or 50 μmol amiloride (inhibitor of macropinocytosis) for 30 min at 37°C [25]. Then, the cells were incubated with aptamers for 40 min at 37°C.…”
Section: Endocytosis Pathway Analysismentioning
confidence: 99%